A corpus-based analysis of the concessive construction just because X doesn't mean Y - Wang, Wen; Wu, Xue (Southern African linguistics and applied language studies, 2022)
This study investigates syntactic and semantic features of the English concessive construction just because X doesn't mean Y (JB-X DM-Y) grounded in Goldberg's theory of construction grammar. Based on initial data collected from the British National Corpus (BNC) and the Corpus of Contemporary American English (COCA), our qualitative analysis proved that: (1) syntactically, there should be an unexpressed pronoun it or that serving as the subject of the DM-Y part. The quantitative analysis revealed the productivity of JB-X DM-Y. In terms of vocabulary, just and mean in the construction can be replaced by the adverb simply and verbs indicating inference or making assertions. In terms of structure, JB-X NEG-VP and JB-X NEG-CLAUSE were widely used, and JB-X QUESTION exhibited certain productivity; and (2) semantically, JB-X DM-Y should be seen as the negation of the construction Y, because X. It presented the meaning of inference denial and concessive meaning, corresponding to the inferential-because construction and causal-because construction. This article provides a systemic discussion about JB-X DM-Y and hopes to provide a basic structure for the future analysis of JB-X DM-Y.